AN ANALYSIS OF BUSINESS COMPETITION AND ISLAMIC BUSINESS ETHICS: SURVIVAL STRATEGIES OF THRIFTY TRADERS IN A METRO CITY - Mujib Baidhowi, Muhammad; Triwibowo, Ananto; Agustiana, Sinta (CV. Lafadz Jaya, 2024)
This study aims to analyze the survival strategies applied by thrifting traders in Metro City in the face of increasingly fierce business competition, as well as to evaluate the application of Islamic business ethics among these traders. The method used is descriptive qualitative, with data collection through interviews and documentation with thrifting traders in Metro City. The results showed that Raina Thrift Shop, Valents.store, and Klamby Second_id apply survival strategies in the form of divestment, reduction, and promotion through social media. In the aspect of Islamic business ethics, the overall implementation of ethics is quite good. However, some weaknesses were found Valents. store does not show responsibility for mistakes in the purchasing process, while Klamby Second_id is not fair to all consumers. In contrast, Raina Thrift Shop has implemented all the principles of Islamic business ethics well. The findings provide important insights for the development of strategies and ethics in the thrifting industry in Metro City.